2017
DOI: 10.3390/children4040022
|View full text |Cite
|
Sign up to set email alerts
|

Mind–Body Interventions for Pediatric Inflammatory Bowel Disease

Abstract: Pediatric inflammatory bowel disease is an autoimmune disease that causes chronic inflammation of the gastrointestinal mucosa. There is emerging evidence that the brain-gut connection affects inflammatory bowel disease (IBD) patients more than previously thought. This is evidenced by comorbid mood disorders, irritable bowel symptoms concurrent with quiescent IBD, and the potential of psychosocial stressors to trigger IBD flares. Mind-body interventions such as psychotherapy, relaxation, mindfulness, biofeedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…symptoms experienced significant improvements in quality of life. The review reported that the findings about the efficacy of mindfulness interventions in IBD were inconclusive, that these interventions might be useful in subgroup of IBD patients with IBS symptoms and that further research of higher methodological quality was needed.Two narrative reviews reported similar findings [18,19].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…symptoms experienced significant improvements in quality of life. The review reported that the findings about the efficacy of mindfulness interventions in IBD were inconclusive, that these interventions might be useful in subgroup of IBD patients with IBS symptoms and that further research of higher methodological quality was needed.Two narrative reviews reported similar findings [18,19].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…There has been a growing body of evidence proving the role of psychosocial factors in the aetiology, maintenance, and exacerbation of FGIDs [3] as well as the use of psychological services as an adjunct to standard medical treatment in producing more favourable outcomes in FGIDs and IBD [5,6]. However, despite clear evidence of the imperative role of clinical psychologists in this field, there remains a gap between the need and provision of clinical psychology services in paediatric gastroenterology centres.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chronic GI conditions like inflammatory bowel diseases (IBD) have also been shown to be exacerbated by psychological stress [4]. Hence, the role of both psychological assessment and intervention in paediatric gastroenterology has been increasing and integration of clinical psychology into standard care has proven to further reduce symptoms and disability associated with both FGID and IBD [5,6]. Yet, its importance seems to be insufficiently recognized and there is still a major lack of availability.…”
Section: Introductionmentioning
confidence: 99%
“…As you become more familiar with the exercise, you may find you are able to complete it in 20 minutes or less (Zeichner, 2018). 22 and Excel application (2010).Independent t-test was used to compare between case and control groups in the mean differences clinical activity for the evaluation of patients with chronic colitis. Moreover, paired sample t test was also used to compare within each group.…”
Section: Progressive Muscle Relaxation Technique: It Involves the Folmentioning
confidence: 99%